2011
DOI: 10.1007/s00248-011-9893-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Archaeal amoA Genes Outnumber Bacterial amoA Genes in Municipal Wastewater Treatment Plants in Bangkok

Abstract: The contribution of ammonia-oxidizing archaea (AOA) to nitrogen removal in wastewater treatment plants (WWTPs) remains unknown. This study investigated the abundance of archaeal (AOA) and bacterial (ammonia-oxidizing bacteria (AOB)) amoA genes in eight of Bangkok's municipal WWTPs. AOA amoA genes (3.28 × 10(7) ± 1.74 × 10(7)-2.23 × 10(11) ± 1.92 × 10(11) copies l(-1) sludge) outnumbered AOB amoA genes in most of the WWTPs even though the plants' treatment processes, influent and effluent characteristics, remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Although higher abundance of AOA relative to AOB has been observed in many habitats, such as soil (19), ocean (3) and artificial environments (28), distinctly different results of the relative abundance of AOA and AOB have been reported in freshwater sediments, and the influencing environmental factors are not well known. It was found that AOA were far more abundant than AOB in the sediments of the Qiantang River, Lake Taihu, freshwater lakes in northwest Germany and the Pearl River Estuary (20, 26, 32, 58), while higher AOB abundances were observed in the sediments of the Chongming eastern tidal flat, Qinghai Lake, and mangrove (24, 31, 64).…”
Section: Discussionmentioning
confidence: 99%
“…Although higher abundance of AOA relative to AOB has been observed in many habitats, such as soil (19), ocean (3) and artificial environments (28), distinctly different results of the relative abundance of AOA and AOB have been reported in freshwater sediments, and the influencing environmental factors are not well known. It was found that AOA were far more abundant than AOB in the sediments of the Qiantang River, Lake Taihu, freshwater lakes in northwest Germany and the Pearl River Estuary (20, 26, 32, 58), while higher AOB abundances were observed in the sediments of the Chongming eastern tidal flat, Qinghai Lake, and mangrove (24, 31, 64).…”
Section: Discussionmentioning
confidence: 99%
“…was the first to report detection of AOA in five plants with low dissolved oxygen (DO) level and long retention time 7 , which suggested potential application of AOA to oxidize ammonia with less DO and consequently low energy consumption. Since then, the presence of AOA has been confirmed in a number of WWTPs worldwide, and the abundances of AOA even outnumbered that of AOB in some of those plants 8 9 10 . However, AOA was not widespread in WWTPs as AOB, as Mussmann’s study showed that AOA was only detected in 4 out of total 52 plants 9 .…”
mentioning
confidence: 99%
“…Studies on the relative abundance of AOA and AOB in wastewater treatment systems have been undertaken in recent years (for a review, see ref. 50 ), and information on this subject is fragmentary and controversial ( 42 , 60 , 67 , 76 , 80 , 82 , 83 ).…”
mentioning
confidence: 99%